Respostas

2014-05-23T11:26:14-03:00
A)(x-2)(x-2)
x²-2x-2x+4
x²-4x+4
3(x²-4x+4)=12
3x²-12x=0
Δ=-12²-4.3.0
Δ=144
x=12+-12/6
x'=0
x''4
s={0,4}


2014-05-23T11:41:29-03:00
A) 3(x-2)² = 12 ⇒ (x-2)² = 4 ⇒ x²-4x+4 = 4 ⇒ x²-4x=0 ⇒ x(x-4)=0 ⇒ então:
    x=0  ou  x=4 ⇒  Solução (S):  S = {0 ; 4}
b) -2x²-10x=0 ⇒ 2x(-x-5)=0 ⇒ ⇒  S = {0;-5}
c)  7x²+13-2=0 ⇒ 7x²+11=0 ⇒  Δ=308 ⇒ x(-0-+√308)/14 ⇒ x'=-√308/14 ou x"=√308/14
                                                  S = {-√308/14;√308/14} 
d) 6x²-x-2=0 ⇒ Δ=49 ⇒ x'=(1-+√49)/12 ⇒ x'=(1-7)/12 = -6/12 = -1/2 ou x"=      (1+7)/12=8/12= 2/3 ⇒                 S={-1/2 ; 2/3}